Solve for the unknown in the equation.

6B + 2B – 7 = 25

**Solution:-**

Add the known value to both sides of the equation.

6B + 2B – 7 (7) = 25 + (7)

Now simplify.

6B + 2B = 32

Combine the unknown-value addends.

8B = 32

Divide both sides of the equation by the known factor to isolate the unknown value.

Now simplify

B = 4

Check the solution by substituting the answer in the original equation and verifying that a true statement results.

The answer checks, so the solution of the equation is 4.